Effectiveness of Peer Counseling Training Module Approach Prophetic Counseling to Improve the Self-Efficacy of Students - Nurani, Pertiwi; Mauliani, Ilma; Jaelani, Nur Safira Paradila; Lestari, Depi (Indonesian Journal of Educational Studies, 2025)
Self-efficacy is a crucial component for Islamic Guidance and Counseling Education students as prospective professional counselors. However, field research indicates that many students still experience anxiety and doubt when practicing counseling skills. This study aims to test the effectiveness of a peer counseling training module using a peer-to-peer approach. Prophetic Counseling in improving the self-efficacy of BKPI students at Muhammadiyah University of Makassar. This approach integrates prophetic values, namely Siddiq, Amanah, Tabligh, And Fathanah into basic counseling skills. This study uses a quantitative approach with a pre-experimental design, specifically using One Group Pre-test Post-test Design. The sampling technique uses a whole group approach (intact group), involving 24 students as a single experimental group. Data collection was conducted using the Counselor Self-Efficacy Scale instrument. Data analysis used the Paired Sample T-Test. The descriptive results of the study showed an increase in the average self-efficacy score of participants from 135.58 at the time pretest to 164.04 on posttest. The results of the hypothesis test prove a significance value of 0.000 (p < 0.05), which means H0 is rejected and Ha is accepted. It can be concluded that the intervention in the form of module training Prophetic Counseling definitively and significantly proven to be able to increase the self-efficacy of BKPI study program students